PERANAN DAN BENTUK TORTOR PADA PEMENTASAN OPERA BATAK DI PUSAT LATIHAN OPERA BATAK PLOt)PEMATANG SIANTAR - Devi Lasroha Sinaga (Gesture: Jurnal Seni Tari, 2016)
This study aims to determine the form of presentation of operas Batak, to describe a way of presenting opera Batak, to describe the form of presentation tortor, and to know the role tortor in staging opera Batak. The theoretical foundation of this research rests on several theories studied, namely the theory of presenting opera Batak, tortor presentation shape theory and theory of the role, with the conceptual framework as a translation problem contained therein. This research was conducted in the street Bah Bolon Kiri (Lorong IV) No. 96 Siantar, in December 2015 to February 2016. The method in this research use descriptive qualitative research methods. The population in this study were 1 informants who are knowledgeable about dance (tortor) in staging opera Batak, 1 director, 1 music player, and the first person who joins the cast in the opera Batak, the number of samples to be studied amounted to 4 people. Data collected through observation, interviews, documentation, and literature study. The results of this study indicate that the form of presentation of opera Batak has important elements, namely: a play (drama), dialog, music (gondang), song (ende) and dance (tortor). Tortor the form of presentation of operas Batak presented three times, at the beginning, middle and end of the scene. Tortor role in staging opera Batak serve to embellish what is dictated by the script becomes symbolic, ensuring variation in the opera  aesthetics, strengthening the scene / act story, become entertainment and become transition between scenes